THE CLINICAL CHARACTERISTICS OF ELDERLY PATIENTS WITH OBSTRUCTIVE SLEEP APNEA SYNDROME AT FRIENDSHIP HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical characteristics of elderly patients with obstructive sleep apnea syndrome at Friendship Hospital.Subjects and methods: A cross-sectional descriptive study was conducted on 46 elderly patients with obstructive sleep apnea syndrome who were examined and diagnosed at the Respiratory and Allergy Department, Friendship Hospital from January 2023 to January 2025.Result: The average age of the study group was 74.28 ± 7.64, with the youngest being 60 years old and the oldest 96 years old. The proportion of males (87%) was higher than females (13%). Common comorbidities with obstructive sleep apnea included hypertension (76.1%), diabetes mellitus (43.5%), dyslipidemia (43.5%), and atherosclerosis (30.4%). The most common clinical symptoms in elderly individuals with obstructive sleep apnea syndrome are: restless sleep (78.3%), snoring (76.1%), sleep-related disturbances (56.5%), and excessive daytime sleepiness (39.1%). Up to 56.53% of elderly individuals with obstructive sleep apnea had a normal BMI, while 41.3% were overweight. Neck circumference over 40 cm accounted for 95.65%, and 4.35% had a neck circumference ≤ 40 cm. The average AHI was 8.77 ± 17.37, with 86.96% experiencing moderate to severe sleep apnea. The Epworth questionnaire for assessing excessive daytime sleepiness has difficulty accurately evaluating the severity of excessive daytime sleepiness in the elderly. The STOP-BANG questionnaire has proven useful in screening for obstructive sleep apnea in the elderly.Consclusion: Common symptoms include poor sleep quality, daytime sleep apnea, and excessive daytime sleepiness, with some individuals experiencing sleep apnea. Elderly individuals may develop obstructive sleep apnea syndrome even with a normal BMI and neck circumference ≤ 40 cm.
Keywords: Obstructive sleep apnea, STOP-BANG questionnaire.